Caesar Act Between American Sovereign Right And International Economic Crime - أحمد بسام; سلامي حمزة (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The " Caesar Syria Civilian Protection Act Of 2019" By which the United States of America targeted to paralyze the Syrian economy is a form of unilateral coercive measures of an economic nature or the so-called unilateral economic sanctions, which are subject to the international economic law that regulates international economic relations given that they are a Negative aspect of those relationships. If the United States is taking advantage of the absence of a normative international agreement that prohibits these measures despite their dangerous effects and its argument is that issuing this law and the like is an American right derived from the principle of economic sovereignty, then other sources of international economic law rules refute this argument, as they impose restrictions on sovereignty The economic nature of states, including the inadmissibility of resorting to unilateral coercive measures of an economic nature due to their violation of many important international principles.